Exploring the meanings of male partner involvement in the prevention of MTCT of HIV in Zimbabwe - Chibango, Vimbai (HTS teologiese studies, 2020)
Male partner involvement (MPI) in the prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV) is considered as one of the priority interventions in reducing paediatric HIV. However, there is neither a standard definition nor measurement for MPI in PMTCT. The study explored meanings of MPI in PMTCT programmes in Zimbabwe. Eight focus group discussions (FGDs) were conducted with men and women aged 18 years and above. Seven key informants (KII) from health institutions and organisations providing PMTCT services were interviewed. Eight in-depth interviews (IDIs) were conducted with pregnant women at two public health facilities. Thematic analysis was used for data analysis. Five major themes were identified which facilitated our understanding of MPI. Male partner involvement was referred to as participation of male partners in HIV couple counselling and testing. Acceptance of condom use during pregnancy and breastfeeding was deemed vital as this prevents HIV transmission. Male partners were expected to have knowledge of administering antiretroviral drugs to an HIV-exposed child. Provision of financial support was another form of male involvement commonly expected during antenatal and postnatal periods. Faithfulness in marriage was a major theme that was highlighted, especially by respondents in marital relationships. Male partner presence in PMTCT community educational sessions was also considered. However, the provision of male-oriented educational programmes was identified as poor. The study suggested a definition for MPI in PMTCT in Zimbabwe. The merit of this definition was that it took a holistic approach to include activities beyond antenatal activities and HIV testing. Future research should explore how public health institutions could create male-oriented health services within PMTCT programmes, as this has the potential of increasing men’s involvement in PMTCT of HIV.Contribution: This article contributed to the knowledge on how world views, which is shaped by culture and religion, influenced the formation of meanings on MPI PMTCT programmes.